Utilization of near infrared reflectancefor the determination of fat, moisture,and protein in cheddar cheese - G.S. Zink; I.J. Jeon; L.H. Harbers (Kansas Agricultural Experiment Station Research Reports, 1989)
Near infrared reflectance spectroscopy (NIRS) was used to develop calibration equations for the rapid determination of moisture, protein, and fat in Cheddar cheese. Most mean values from NIRS data had lower standard deviations than values obtained by standard laboratory procedures. A larger number of samples is needed to refine calibrations and validate the equations.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; Fat; Moisture; Protein; Cheese; Near infrared reflectance spectroscopy (NIRS)